2017
DOI: 10.2196/resprot.8856
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Match Young Black Men and Transwomen Who Have Sex With Men or Transwomen to HIV Testing Options (All About Me): Protocol for a Randomized Controlled Trial

Abstract: BackgroundHIV testing is a critical component of HIV prevention and care. Interventions to increase HIV testing rates among young black men who have sex with men (MSM) and black transgender women (transwomen) are needed. Personalized recommendations for an individual’s optimal HIV testing approach may increase testing.ObjectiveThis randomized trial tests the hypothesis that a personalized recommendation of an optimal HIV testing approach will increase HIV testing more than standard HIV testing information.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Although not sought out specifically in the process of conducting this review, many protocols have been identified for continued research into the development of digital health interventions [ 107 - 112 ]. The development of digital health interventions for LGBTIQ+ young people is a burgeoning field of study, and we expect the evidence base to advance quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Although not sought out specifically in the process of conducting this review, many protocols have been identified for continued research into the development of digital health interventions [ 107 - 112 ]. The development of digital health interventions for LGBTIQ+ young people is a burgeoning field of study, and we expect the evidence base to advance quickly.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 43 , 51 , 52 , 57 , 58 , 64 , 71 , 76 , 78 , 79 Most studies were implemented after 2000. 20 26 , 34 37 , 39 79 , 81 …”
Section: Resultsmentioning
confidence: 99%
“… 43 , 53 , 54 , 65 , 71 , 74 , 78 , 79 , 81 Thirty-one interventions were evaluated by RCTs. 20 , 21 , 23 , 26 , 35 , 36 , 38 , 42 44 , 49 51 , 53 , 54 , 57 , 59 , 64 , 65 , 67 , 68 , 71 76 , 78 81 Eleven studies were evaluated by using a quasi-experimental design; 24 , 25 , 33 , 34 , 39 , 41 , 45 , 47 , 55 , 60 , 61 5 of the 11 used a pretest-posttest design. 24 , 25 ...…”
Section: Resultsmentioning
confidence: 99%
“…There is a significant need for in‐group healthcare providers (Hudson, 2019; Poteat et al, 2019; Salerno et al, 2019), particularly as participants sought out providers who matched their racial/ethnic and/or gender identity (Howard et al, 2019; Hudson, 2019). When examining interventions around HIV preventative measures that do not include PrEP, the literature suggested that interventions be aimed at testing (Bukowski et al, 2018), be culturally sensitive, and tailored to the individual (Koblin et al, 2017; MacCarthy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%